From Theory to Practice: Examining the Link Between Classroom Learning on Gender and Advocacy Engagement - Montano, Mary Rose; Opeña, Anna Rhea C.; Ilao, Jeanne Mae; Orajay, Julie Ann A.; Garma, Marilyn R.; Reyes, Kathleen R. (RSF Conference Series: Business, Management and Social Sciences, 2025)
Education plays a vital role in shaping students’ values and behaviors, particularly regarding gender equality and social justice. In response to the growing call for advocacy-based learning, this study examines the impact of classroom instruction in the Gender and Society course on students’ engagement in gender advocacy. Specifically, it explores how pedagogical approaches influence students’ awareness, motivation, and real-world application of advocacy skills. Employing a descriptive quantitative research design, data were collected from 164 students through a self-constructed, validated survey using Likert-scale items. Descriptive statistics and Pearson’s R correlation analysis were used to interpret the results. Findings reveal that the course significantly enhanced students’ attitudes and motivation toward gender advocacy (grand mean = 4.68; SD = 0.54). Contributing factors included interactive teaching methods, relevant content, and instructor support (grand mean = 4.53). While some barriers, such as limited opportunities and lack of knowledge, were identified (grand mean = 3.10), they did not significantly impede advocacy participation. A strong correlation was found between teaching methods and motivation (r = 0.640), and a moderate correlation with real-life advocacy application (r = 0.522). The study underscores the transformative potential of gender-responsive pedagogy in promoting critical thinking, empathy, and active citizenship. It recommends integrating experiential learning, collaborative projects, and community engagement to sustain student involvement in advocacy. Despite limitations related to sample scope and reliance on self-reported data, the research contributes valuable insights into how gender education can catalyze social change.